2018
DOI: 10.1038/s41564-017-0091-5
|View full text |Cite
|
Sign up to set email alerts
|

A pathway for biological methane production using bacterial iron-only nitrogenase

Abstract: Methane (CH) is a potent greenhouse gas that is released from fossil fuels and is also produced by microbial activity, with at least one billion tonnes of CH being formed and consumed by microorganisms in a single year . Complex methanogenesis pathways used by archaea are the main route for bioconversion of carbon dioxide (CO) to CH in nature. Here, we report that wild-type iron-iron (Fe-only) nitrogenase from the bacterium Rhodopseudomonas palustris reduces CO simultaneously with nitrogen gas (N) and protons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
167
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(183 citation statements)
references
References 42 publications
6
167
2
Order By: Relevance
“…Studies have shown that methanogens are found in colonic samples at rates ranging from < 10 3 to over 10 9 CFUÁg À1 stool [30]. Recently, a new pathway of methane formation was discovered that uses bacterial iron-only nitrogenase to generate methane from CO 2 [31]. The iron-iron (Feonly) nitrogenase from Rhodopseudomonas palustris was found to simultaneously carry out the following reductions: CO 2 > CH 4 ; N 2 > NH 3 and 2H À > H 2 .…”
Section: Short-chain Fatty Acid Production In the Large Intestinementioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that methanogens are found in colonic samples at rates ranging from < 10 3 to over 10 9 CFUÁg À1 stool [30]. Recently, a new pathway of methane formation was discovered that uses bacterial iron-only nitrogenase to generate methane from CO 2 [31]. The iron-iron (Feonly) nitrogenase from Rhodopseudomonas palustris was found to simultaneously carry out the following reductions: CO 2 > CH 4 ; N 2 > NH 3 and 2H À > H 2 .…”
Section: Short-chain Fatty Acid Production In the Large Intestinementioning
confidence: 99%
“…The iron-iron (Feonly) nitrogenase from Rhodopseudomonas palustris was found to simultaneously carry out the following reductions: CO 2 > CH 4 ; N 2 > NH 3 and 2H À > H 2 . Fe-only nitrogenase is found in diverse microorganisms and may play an important role in regulating microbial community structure by providing CH 4 to anaerobic CH 4 -metabolizing archaea and aerobic methanotropic bacteria which can be used as a carbon and energy source [31].…”
Section: Short-chain Fatty Acid Production In the Large Intestinementioning
confidence: 99%
“…MAG 1 is able to carry out the CO2 fixation via the Calvin-Benson cycle under anaerobic conditions (Table S7). In this process, CO2 and ribulose bisphosphate (5-carbon sugar) are transformed into 3-phosphoglycerate (Zheng et al, 2018). Interestingly, no other microorganisms of the community showed a phototrophic metabolism or presented (Sato et al, 2007).…”
Section: Functional Novelty and Implicationsmentioning
confidence: 99%
“…The evolutionary processes have generated way more lineages and lifestyles than are known, and in acknowledgement of this, the literature speaks of the extent of undiscovered ‘microbial dark matter’ (Rinke et al ., ). As omic efforts uncover more and more lineages (Castelle and Banfield, ), so do discoveries (not all omics‐based) of unexpected microbial ‘lifestyles’ – nitrogen‐fixing bacteria producing methane (Zheng et al ., ), Antarctic soil bacteria scavenging atmospheric hydrogen (Ji et al ., ), filamentous sediment bacteria transporting electrons over centimetre distances (Pfeffer et al ., ), Antarctic membrane vesicle encapsulated archaeal plasmids disseminating like viruses (Erdmann et al ., ) – lots of wonderful examples. So, one wise step forward would be to resist using pigeon‐holed expectations and instead let the systems openly report back about which microbes are present, what they are doing and how they are being so extraordinary.…”
Section: Illustrations Of Differences Between Environmental and Physimentioning
confidence: 99%